The Economic Impact Of The Presence Of Oil Palm Plantations Towards ISPO Certification: Case Study Of Jaya Usaha Sempurna Producer Cooperative In Mega Timur Village - Rudi Hartono (International Journal of Management and Business Economics, 2025)
Jaya Usaha Sempurna Producer Cooperative located in Mega Timur Village, Sungai Ambawang Sub-district, Kubu Raya District, West Kalimantan, is seeking Indonesian Sustainable Palm Oil (ISPO) certification to improve the competitiveness and sustainability of their oil palm plantation. This study aims to analyze the economic impact of the presence of oil palm plantations towards ISPO certification, as well as its influence on the welfare of farmers, cooperative members, and the surrounding community. The method used is a qualitative approach with direct observation and in-depth interviews with farmers and cooperative members. The results show that ISPO certification provides an increase in farmers' income through better selling prices, and encourages sustainability in oil palm plantation practices. However, challenges such as certification costs and farmers' understanding of ISPO principles need to be addressed to achieve optimal results.